Left Main Stem Compression by Intrapericardial Paraganglioma Associated With Succinate Dehydrogenase Mutation - Xue Wang, MB BChir; Mohsin Gondal, MBBS; Samer Alabed, MD; Catherine Hill, MB ChB; David Barmby, MB ChB (JACC: Case Reports, 2024)
Paragangliomas are rare extra-adrenal tumors originating from chromaffin cells. We discovered a large intrapericardial mass confirmed to be a primary cardiac paraganglioma encasing the left main stem coronary artery in a 38-year-old woman who presented with dyspnea and subscapular pain. Genetic predisposition related to succinate dehydrogenase A mutation was identified.